Oculo-auriculo-vertebral spectrum: a review of the literature and genetic update. Issue 10 (12th August 2014) - Beleza-Meireles, Ana; Clayton-Smith, Jill; Saraiva, Jorge M; Tassabehji, May
Abstract : Oculo-auriculo-vertebral spectrum (OAVS, OMIM 164 210) is a developmental disorder primarily involving structures derived from the first and second pharyngeal arches during embryogenesis. The phenotype is clinically heterogeneous and is typically characterised by abnormal development of the ear, mandible anomalies and defects of the vertebral column. OAVS may occur as a multiple congenital abnormality, and associated findings include anomalies of the eye, brain, heart, kidneys and other organs and systems. Both genetic and environmental factors are thought to contribute to this craniofacial condition, however, the mechanisms are still poorly understood. Here, we present a review of the literature on OAVS, discussing what is known about the aetiology, candidate loci, possible mechanisms and the range of clinical features that characterise this condition. We also comment on some important aspects of recurrence risk counselling to aid clinical management.